Emotion and Attention Effects: Is It All a Matter of Timing? Not Yet - Pessoa, Luiz (Frontiers in Human Neuroscience, 2010)
Controversy surrounds the relationship between emotion and attention in brain and behavior. Two recent studies acquired millisecond-level data to investigate the timing of emotion and attention effects in the amygdala (Luo et al., 2010; Pourtois et al., 2010). Both studies argued that the effects of emotional content temporally precede those of attention and that prior discrepancies in the literature may stem from the temporal characteristics of the functional MRI signal. Although both studies provide important insights about the temporal unfolding of affective responses in the brain, several issues are discussed here that qualify their results. Accordingly, it may not be yet time to accept the conclusion that “automaticity is a matter of timing”. Indeed, emotion and attention may be more closely linked than suggested in the two studies discussed here.